Cognate interaction with CD4+ T cells instructs tumor-associated macrophages to acquire M1-like phenotype - Eisel, David; Das, Krishna; Dickes, Elke; König, Rainer; Osen, Wolfram; Eichmüller, Stefan B. (Frontiers in immunology, 2019)
The immunosuppressive tumor microenvironment (TME) established by tumor cells, stromal cells and inhibitory immune cells counteracts the function of tumor reactive T cells. Tumor associated macrophages (TAMs) showing functional plasticity contribute to this process as so called M2-like macrophages can suppress the function of effector T cells and promote their differentiation into regulatory T cells (Tregs). Furthermore, tumor antigen specific CD4+ T effector cells can essentially sustain anti-tumoral immune responses as shown for various tumor entities, thus suggesting that cognate interaction between tumor antigen-specific CD4+ T cells and TAMs might shift the intra-tumoral M1/M2 ratio towards M1. This study demonstrates repolarization of M2 like PECs upon MHC II-restricted interaction with tumor specific CD4+ T cells in vitro as shown by extensive gene and protein expression analyses. Moreover, adoptive transfer of OVA-specific OT-II cells into C57BL/6 mice bearing OVA expressing IAb-/- tumors resulted in increased accumulation of M1-like TAMs with enhanced M1 associated gene and protein expression profiles. Thus, this paper highlights a so far underestimated function of the CD4+ T cell / TAM axis in re-conditioning the immunosuppressive tumor microenvironment.
Gesehen am 23.07.2019
Im Titel ist "+" hochgestellt